A complete description of Mitracarpus diversifolius (Rubiaceae) reveals new characters for the genus - Nuñez Florentin, Mariela; Salas, Roberto M.; Bezerra De Souza, Elnatan; Cabral, Elsa L. (Phytotaxa, 2017)
A complete description of Mitracarpus diversifolius (Rubiaceae, Spermacoceae) based on morphological features not previously studied and now available from two recent collections, is here presented. Details of fruits and seeds of this species are now known, and some of them are unusual for the genus. The corolla is persistent on mature fruit, and the seeds have a reticulate-foveate exotesta with thickened anticlinal walls and concave periclinal walls. Illustrations and SEM micrographs of these and other characters are also provided.